FindRoot, starting values - numerical-methods

I have a simple system of equations that I am trying to solve numerically,
ClearAll["Global`*"]
b1 = 1
T = 2
t = .5
FindRoot[{(1 - xbar1) 2 ra1 == n1 - (1 - n1)/T,
ra1 == (pa1^2) (b1^2)/pw,
pw == (1 - xbar1) ra1 - 1,
xbar1 == 1/t Log[(t n1 + ra1)/ra1],
t[1 - xbar1] + Log[T] - Log[ra1] + Log[t (1 - n1)/(Exp[t] - 1)] ==
0},
{{n1, .5}, {ra1, .5}, {pa1, .5}, {pw, 1.5}, {xbar1, .5}},
AccuracyGoal -> 11]
This is the output I get,
FindRoot::nlnum: "The function value {0.25,0.333333,2.25,-0.31093,0.432752
+0.5[0.5]} is not a list of numbers with dimensions {5} at
{n1,ra1,pa1,pw,xbar1} = {0.5,0.5,0.5,1.5,0.5}."de here`{n1,ra1,pa1,pw,xbar1} = ` {0.5,0.5,0.5,1.5,0.5}."``
I am wondering if I am not specifying the initial starting values correctly. I did this on a similar problem just using NSolve and I had no problem getting a result so I am stumped to what the problem is here.

Related

OCaml : recursive function dealing with parity between list elements and an int

This function should take two arguments a list and an int. if an element of the list and the number “a” parity is equal then they’d have to be summed, else the two numbers should be subtracted.
The calculation should be done in this order :
At the beginning, the residual value r is the value of a,
Each element e of lst (taken in the order given by the list) affects the residual value: if e and r are of the same parity (both odd or both even) then the new r’ is equal to the sum of r + e, if not then it should be equal to the subtraction of r - e,
The last r is the result expected.
To put this into an example:
par [4;7;3;6] 5
should return -1, it would work as follows :
5 and 4 have a different parity so we subtract -> 5 - 4 = 1
1 and 7 are both odd, so we add them together -> 1 + 7 = 8
8 and 3 have a different parity -> 8 - 3 = 5
Finally, 5 and 6 have different parity -> 5 - 6 = -1
I have thought of something like this below :
let rec par lst a =
match lst with
| [] -> 0
| h::t -> if (h mod 2 == 0 && a mod 2 == 0) || (h mod 2 == 1 && a mod 2 == 1) then a + h
| h::t -> if (h mod 2 == 0 && a mod 2 == 1) || (h mod 2 == 1 && a mod 2 == 0) then a - h :: par t a ;;
EDIT1 : Here is the error I get from the compiler :
Line 4, characters 83-88: Error: This expression has type int but an
expression was expected of type unit because it is in the result of a
conditional with no else branch
The idea is to build this function using no more than the following predefined functions List.hd, List.tl et List.length.
What is disturbing in my proposition above and how to remediate it? Anyone can help me resolve this, please?
EDIT 2:
I was able to do what is needed with if...then... else syntax (not the best I know for OCaml) but I personally have more difficulties sometimes understanding the pattern matching. Anyhow here's what I got :
let rec par lst a = (* Sorry it might hurt some sensible eyes *)
if List.length lst = 0 then a
else
let r = if (List.hd lst + a) mod 2 == 0 then (a + (List.hd lst))
else (a - (List.hd lst)) in
par (List.tl lst) r ;;
val par : int list -> int -> int = <fun>
Suggestions and help to put it into a pattern-matching syntax are welcomed.
Your code doesn't compile. Did you try compiling it? Did you read the errors and warnings produced by the compiler? Could you please add them to your question?
A few comments about your code:
| h::t -> if ... then ... should be | h::t when ... -> ...;
(h mod 2 == 0 && a mod 2 == 0) || (h mod 2 == 1 && a mod 2 == 1) can be simplified to (h - a) mod 2 == 0;
The compiler likes to know that the matching was exhaustive; in particular, you don't need to repeat the test in the third line of the matching (the third line will only be read if the test was false in the second line);
You are missing the recursive call in the second line of the matching;
In the third line of the matching, you are returning a list rather than a number (the compiler should have explicitly told you about that type mismatch!! did you not read the compiler error message?);
In the first line of the matching, in case the list is empty, you return 0. Are you sure that 0 is the value you want to return, when you've reached the end of the list? What about the residual value that you have calculated?
Once you have fixed this version of your code as a recursive function, I recommend trying to write a code solving the same problem using List.fold_left, rather than List.hd and List.tl as you are suggesting.
When I first wrote my answer, I included a fixed version of your code, but I think I'd be doing you a disservice by handing out the solution rather than letting you figure it out.

Sequence function error?

I'm getting an error on line 3 "TypeError: 'int' object is not iterable," and its been bothering me. Any advice/fixes appreciated.
Example test: collatz_counts(4) → 3 # 4 -> 2 -> 1 (3 steps)
Code I have:
def collatz_counts(x):
num = 0
for i in (x):
if i == 1:
num += 1
return num
elif i % 2 == 0:
num(i) / 2
num += 1
num.append(i)
else:
num = (i*2) + 3
num += 1
num.append(i)
return num
This can be solved recursively:
def collatz_length(n):
if n == 1:
return 1
return 1 + collatz_length(3*n+1 if n%2 else n//2)
Which lends itself to be memoized if you are going to be calling for a range of numbers, e.g. in Py3
import functools as ft
#ft.lru_cache(maxsize=None)
def collatz_length(n):
if n == 1:
return 1
return 1 + collatz_length(3*n+1 if n%2 else n//2)
Which will run through the first million collatz sequences in about 2.31s vs about 28.6s for the iterative solution.
Use a while loop. Just modify x in place until you get to 1 and keep track of the number of steps each time you run a cycle.
def collatz_counts(x):
steps = 0
while x != 1:
if x % 2:
x = x * 3 + 1
else:
x = x // 2
steps += 1
return steps

Why does the fibonacci recursive sequence work?

I am wondering why this Fibonacci recursive function works:
int fibRec(int n)
{
if ((n == 1) || (n == 0))
{
return n;
}
int i = fibRec(n - 1) + fibRec(n - 2);
return i;
}
I understand what the Fibonacci sequence is and I understand what a recursive function does and how this function is working. I'm just having troubles understanding why it works. I know that when you break it down, you are essentially adding a bunch of 0s and 1s, as this image depicts.
fibonacci recursive
But why is it that when I pass a 5 to the function and all the 0 and 1s are added that it will equal the 5th sequence number in the Fibonacci sequence? I've seen this question asked before but never really explained. The responses are all just "because recursion". Yes, I know what a recursive function is and how this one is working. But WHY does this recursive function give you the correct Fibonacci sequence number?
In the Fibonacci sequence the first two numbers are zero and one. Every number after these is the sum of the previous 2 numbers. So the first few numbers are
F(0) ≡ 0
F(1) ≡ 1
F(2) = F(1) + F(0) = 1 + 0 = 1
F(3) = F(2) + F(1) = 1 + 1 = 2
F(4) = F(3) + F(2) = 2 + 1 = 3
F(5) = F(4) + F(3) = 3 + 2 = 5
F(6) = F(5) + F(4) = 5 + 3 = 8
...
F(n) = F(n - 1) + F(n - 2) ∀ n > 1
Therefore when we calculate a Fibonacci number recursively we have to practice the following logical procedure (in pseudo-code out of respect to StackOverflow).
Integer NthFibonacci(Integer n) {
if (n < 0) {
return undefined;
} else if (n < 2) {
return n;
} else {
return NthFibonacci(n - 1) + NthFibonacci(n - 2);
}
}
I'm sure you know all this but I think it will help my explanation to have this part as a reference.
Where the Ones and Zeros Come In
The best way to explain this is probably with an example.
Imagine that, as above, we are trying to recursively calculate F(6). Try following the procedure given above. Remember that we will perform recursion only if n > 1.
First we start with F(6) = F(5) + F(4).
Then we find F(5) = F(4) + F(3).
Then we find F(4) = F(3) + F(2).
Then we find F(3) = F(2) + F(1).
Then we find F(2) = F(1) + F(0).
This is where things start to work out!
We have now gotten F(2) in terms of F(1) ≡ 1 and F(0) ≡ 0 (both of which are known), and so we are able to calculate an actual value instead of performing more recursion.
We can now find F(2) = F(1) + F(0) = 1 + 0 = 1.
NOTICE THE 1 AND 0 Those are what people are talking about when they say the whole thing comes down to ones and zeros. Every time we recurse down to find a base value we will end up finding F(2) = 1 + 0. This leads to more ones and zeros as we move back up our recursion tree being able to calculate higher and higher values, as follows.
F(3) = F(2) + F(1) = (1 + 0) + 1
F(4) = F(3) + F(2) = ((1 + 0) + 1) + (1 + 0)
F(5) = F(4) + F(3) = (((1 + 0) + 1) + (1 + 0)) + ((1 + 0) + 1)
F(6) = F(5) + F(4) = ((((1 + 0) + 1) + (1 + 0)) + ((1 + 0) + 1)) + (((1 + 0) + 1) + (1 + 0))
Now if you add up all the 1's you get a sum of 8, and so F(6) = 8, which is correct!
This is how it works, and this is how it breaks down to ones and zeros.
Remember, recursion works by breaking down the problem till we know what the answer is, and then building it up from there.
What do we know about the fibonacci sequence?
We know that when:
x = 1
and
x = 0
That that is the lowest it goes. That is an important key. Because when x = 0 we are really doing 0 + 0 and when x = 1 we are really doing 0 + 1. Now start at the top.
0,1,1,2,3,5,8,13...
If we are at 13. what is 13? Why simply 5 + 8 right? So That is where
int i = fibRec(n - 1) + fibRec(n - 2);
comes from. Because these are going to branch out lower and lower till we are at a base case for each one.
This is the recursive calling. Because now the method is going to go back to the stack and call fibRec again. You will notice that (n-1) and (n-2) are both added together and set to i. This is so that we don't lose the value. because of the + sign the stack then ends up returning more and more (n-1)s and (n-2)s until we are at the base case. I hope all of this makes sense. Thinking recursively can be very difficult. Here is a a visual representation from top to bottom of what it would look like.
In short. This just keeps adding the previous fibonacci sequences to the current one until it gets to the current loop.

Tweaking a Function in Python

I am trying to get the following code to do a few more tricks:
class App(Frame):
def __init__(self, master):
Frame.__init__(self, master)
self.grid()
self.create_widgets()
def create_widgets(self):
self.answerLabel = Label(self, text="Output List:")
self.answerLabel.grid(row=2, column=1, sticky=W)
def psiFunction(self):
j = int(self.indexEntry.get())
valueList = list(self.listEntry.get())
x = map(int, valueList)
if x[0] != 0:
x.insert(0, 0)
rtn = []
for n2 in range(0, len(x) * j - 2):
n = n2 / j
r = n2 - n * j
rtn.append(j * x[n] + r * (x[n + 1] - x[n]))
self.answer = Label(self, text=rtn)
self.answer.grid(row=2, column=2, sticky=W)
if __name__ == "__main__":
root = Tk()
In particular, I am trying to get it to calculate len(x) * j - 1 terms, and to work for a variety of parameter values. If you try running it you should find that you get errors for larger parameter values. For example with a list 0,1,2,3,4 and a parameter j=3 we should run through the program and get 0123456789101112. However, I get an error that the last value is 'out of range' if I try to compute it.
I believe it's an issue with my function as defined. It seems the issue with parameters has something to do with the way it ties the parameter to the n value. Consider 0123. It works great if I use 2 as my parameter (called index in the function) but fails if I use 3.
EDIT:
def psi_j(x, j):
rtn = []
for n2 in range(0, len(x) * j - 2):
n = n2 / j
r = n2 - n * j
if r == 0:
rtn.append(j * x[n])
else:
rtn.append(j * x[n] + r * (x[n + 1] - x[n]))
print 'n2 =', n2, ': n =', n, ' r =' , r, ' rtn =', rtn
return rtn
For example if we have psi_j(x,2) with x = [0,1,2,3,4] we will be able to get [0,1,2,3,4,5,6,7,8,9,10,11] with an error on 12.
The idea though is that we should be able to calculate that last term. It is the 12th term of our output sequence, and 12 = 3*4+0 => 3*x[4] + 0*(x[n+1]-x[n]). Now, there is no 5th term to calculate so that's definitely an issue but we do not need that term since the second part of the equation is zero. Is there a way to write this into the equation?
If we think about the example data [0, 1, 2, 3] and a j of 3, the problem is that we're trying to get x[4]` in the last iteration.
len(x) * j - 2 for this data is 10
range(0, 10) is 0 through 9.
Manually processing our last iteration, allows us to resolve the code to this.
n = 3 # or 9 / 3
r = 0 # or 9 - 3 * 3
rtn.append(3 * x[3] + 0 * (x[3 + 1] - x[3]))
We have code trying to reach x[3 + 1], which doesn't exist when we only have indices 0 through 3.
To fix this, we could rewrite the code like this.
n = n2 / j
r = n2 - n * j
if r == 0:
rtn.append(j * x[n])
else:
rtn.append(j * x[n] + r * (x[n + 1] - x[n]))
If r is 0, then (x[n + 1] - x[n]) is irrelevant.
Please correct me if my math is wrong on that. I can't see a case where n >= len(x) and r != 0, but if that's possible, then my solution is invalid.
Without understanding that the purpose of the function is (is it a kind of filter? or smoothing function?), I prickled it out of the GUI suff and tested it alone:
def psiFunction(j, valueList):
x = map(int, valueList)
if x[0] != 0:
x.insert(0, 0)
rtn = []
for n2 in range(0, len(x) * j - 2):
n = n2 / j
r = n2 - n * j
print "n =", n, "max_n2 =", len(x) * j - 2, "n2 =", n2, "lx =", len(x), "r =", r
val = j * x[n] + r * (x[n + 1] - x[n])
rtn.append(val)
print j * x[n], r * (x[n + 1] - x[n]), val
return rtn
if __name__ == '__main__':
print psiFunction(3, [0, 1, 2, 3, 4])
Calling this module leads to some debugging output and, at the end, the mentionned error message.
Obviously, your x[n + 1] access fails, as n is 4 there, so n + 1 is 5, one too much for accessing the x array, which has length 5 and thus indexes from 0 to 4.
EDIT: Your psi_j() gives me the same behaviour.
Let me continue guessing: Whatever we want to do, we have to ensure that n + 1 stays below len(x). So maybe a
for n2 in range(0, (len(x) - 1) * j):
would be helpful. It only produces the numbers 0..11, but I think this is the only thing which can be expected out of it: the last items only can be
3*3 + 0*(4-3)
3*3 + 1*(4-3)
3*3 + 2*(4-3)
and stop. And this is achieved with the limit I mention here.

f(n), understanding the equation

I've been tasked with writing MIPS instruction code for the following formula:
f(n) = 3 f(n-1) + 2 f(n-2)
f(0) = 1
f(1) = 1
I'm having issues understanding what the formula actually means.
From what I understand we are passing an int n to the doubly recursive program.
So for f(0) the for would the equation be:
f(n)=3*1(n-1) + 2*(n-2)
If n=10 the equation would be:
f(10)=3*1(10-1) + 2*(10-2)
I know I'm not getting this right at all because it wouldn't be recursive. Any light you could shed on what the equation actually means would be great. I should be able to write the MIPS code once I understand the equation.
I think it's a difference equation.
You're given two starting values:
f(0) = 1
f(1) = 1
f(n) = 3*f(n-1) + 2*f(n-2)
So now you can keep going like this:
f(2) = 3*f(1) + 2*f(0) = 3 + 2 = 5
f(3) = 3*f(2) + 2*f(1) = 15 + 2 = 17
So your recursive method would look like this (I'll write Java-like notation):
public int f(n) {
if (n == 0) {
return 1;
} else if (n == 1) {
return 1;
} else {
return 3*f(n-1) + 2*f(n-2); // see? the recursion happens here.
}
}
You have two base cases:
f(0) = 1
f(1) = 1
Anything else uses the recursive formula. For example, let's calculate f(4). It's not one of the base cases, so we must use the full equation. Plugging in n=4 we get:
f(4) = 3 f(4-1) + 2 f(4-2) = 3 f(3) + 2 f(2)
Hm, not done yet. To calculate f(4) we need to know what f(3) and f(2) are. Neither of those are base cases, so we've got to do some recursive calculations. All right...
f(3) = 3 f(3-1) + 2 f(3-2) = 3 f(2) + 2 f(1)
f(2) = 3 f(2-1) + 2 f(2-2) = 3 f(1) + 2 f(0)
There we go! We've reached bottom. f(2) is defined in terms of f(1) and f(0), and we know what those two values are. We were given those, so we don't need to do any more recursive calculations.
f(2) = 3 f(1) + 2 f(0) = 3×1 + 2×1 = 5
Now that we know what f(2) is, we can unwind our recursive chain and solve f(3).
f(3) = 3 f(2) + 2 f(1) = 3×5 + 2×1 = 17
And finally, we unwind one more time and solve f(4).
f(4) = 3 f(3) + 2 f(2) = 3×17 + 2×5 = 61
No, I think you're right and it is recursive. It seems to be a variation of the Fibonacci Sequence, a classic recursive problem
Remember, a recursive algorithm has 2 parts:
The base case
The recursive call
The base case specifies the point at which you cannot recurse anymore. For example, if you are sorting recursively, the base case is a list of length 1 (since a single item is trivially sorted).
So (assuming n is not negative), you have 2 base cases: n = 0 and n = 1. If your function receives an n value equal to 0 or 1, then it doesn't make sense to recurse anymore
With that in mind, your code should look something like this:
function f(int n):
#check for base case
#if not the base case, perform recursion
So let's use Fibonacci as an example.
In a Fibonacci sequence, each number is the sum of the 2 numbers before it. So, given the sequence 1, 2 the next number is obviously 1 + 2 = 3 and the number after that is 2 + 3 = 5, 3 + 5 = 8 and so on. Put generically, the nth Fibonacci number is the (n - 1)th Fibonacci Number plus the (n - 2)th Fibonacci Number, or f(n) = f(n - 1) + f(n - 2)
But where does the sequence start? This is were the base case comes in. Fibonacci defined his sequence as starting from 1, 1. This means that for our pruposes, f(0) = f(1) = 1. So...
function fibonacci(int n):
if n == 0 or n == 1:
#for any n less than 2
return 1
elif n >= 2:
#for any n 2 or greater
return fibonacci(n-1) + fibonacci(n-2)
else:
#this must n < 0
#throw some error
Note that one of the reasons Fibonacci is taught along with recursion is because it shows that sometimes recursion is a bad idea. I won't get into it here but for large n this recursive approach is very inefficient. The alternative is to have 2 global variables, n1 and n2 such that...
n1 = 1
n2 = 1
print n1
print n2
loop:
n = n1 + n2
n2 = n1
n1 = n
print n
will print the sequence.